Principles of Hip Arthroscopy - Joshua D. Harris (Frontiers Research Topics, 2017)
The field of arthroscopy, originating from Denmark in 1912, has rapidly evolved to diagnose and treat a wide range of musculoskeletal pathologies. Although around for sometime, arthroscopy in the field of orthopedics has traditionally focused on the knee, shoulder, or elbow, as arthroscopy of the hip is technically challenging; the deep structures of the hip, including neurovascular bundles, require specialized training and equipment to access. However, with advances in surgical techniques, hip arthroscopy has become increasingly popular given its ability to treat pathologies with previously poor prognoses such as labral tears, hip arthritis and femoroacetabular impingement (FAI). When indicated, hip arthroscopy results in shorter recovery times, low complication rates, and excellent outcomes in quality of life and pain regardless of age, gender or activity level. The purpose of this e-book is to shed light on this expanding field by delving into the common hip pathology femoroacetabular impingement, its clinical relevance, and to explore various surgical techniques and postoperative rehabilitation. It is our hope that this textbook provides valuable knowledge to advance the field of hip arthroscopy, enhance surgical techniques, and ultimately increase the quality of patient care.